Wear analysis of piston ring / Muhammad Ridzuwan Tukimin, Zaidi Hafizi Zakaria and Nazli Mahmood - Tukimin, Muhammad Ridzuwan; Zakaria, Zaidi Hafizi; Mahmood, Nazli (Faculty of Mechanical Engineering, 2011)
These projects were carrying out because we want to know the materials that were use to make a piston ring. In this project we also will know the type and the effect that happen to piston rings. From this project also, we will learn from metallurgical aspect how the microstructure and hardness changes when heat are applied to the materials. After doing this project, we know that metallurgy and automotives are relevant to each other. This is because, all the materials that we want to use, we have to analyzed the microstructure for the suitable one or the part of the automotives did not have the characteristic of situation.